Treatment of plasma cell dyscrasias with lenalidomide - Dimopoulos, M.A.; Kastritis, E.; Rajkumar, S.V. (Leukemia, 2008)
Lenalidomide is an immunomodulatory drug, structurally related to thalidomide, with pleiotropic activity including antiangiogenic and antineoplastic properties. It is the product of advances in our understanding of the biology of myeloma cells, their interactions with the microenvironment and of the underlying molecular pathways. In preclinical and clinical studies, lenalidomide was more potent and less toxic than thalidomide. Subsequent phase II and III studies confirmed the activity of lenalidomide either as a single agent or in combination with dexamethasone in relapsed or refractory myeloma patients, whereas combinations with chemotherapy induce high response rates and durable remissions. Lenalidomide has been used successfully as an upfront treatment either with high or low dose dexamethasone or with melphalan and prednisone, resulting in high overall response and complete response rates and excellent 1-year survival. Lenalidomide causes less neuropathy than thalidomide; however, the risk of thromboembolism is high, especially in patients treated with lenalidomide and steroids. In this review, we summarize the mechanisms of action, toxicity and clinical activity, and the current role of lenalidomide in patients with multiple myeloma or other related plasma cell disorders.